The Impacts of Risk Management Structure on Efficiency Performance in Politically Connected Malaysian General Insurance Companies - Qian, Long Kweh; Noor Azlinna, Azizan; Irene, Wei Kiong Ting; Wen-Min, Lu (2015)
In today’s challenging business world, insurers should focus on improving their competitive advantages to secure increased profits and reduced costs. This study investigates whether political connections affect the relationship between risk management and the operating efficiency of general insurance companies operating in Malaysia for the period 2008-2011. First, this research applies the two-stage data envelopment analysis (DEA) methodology, decomposing the typical two-stage operating process of general insurance companies: marketing efficiency and profitability efficiency of the sample firms. The sample firms have to first improve their marketing efficiency, and then proceed to improve their profitability efficiency. Second, this study applies panel data regression to test the impact of risk management on general insurers’ performance. Consistent with prior studies, we rerun our regression analysis using Tobit regression. Consistently, we find that risk management only has a negative impact on the operating efficiency of Malaysian general insurers with political connections.